Pengembangan Website Responsive Sebagai Portal Informasi Kegiatan dan Berita Himpunan Mahasiswa Menggunakan Metode Research And Development dengan Model Waterfall - Satria Cahya Syaputra; Cucut Hariz Pratomo (Journal of Information System Research (JOSH), 2026)
The dissemination of activity information and news within Student Associations is often carried out through various separate platforms, resulting in information fragmentation and reducing the effectiveness of information delivery to students. This condition makes it difficult for students to obtain information due to the increased risk of missing important organizational activities and news. Therefore, a centralized information platform is needed to provide integrated information that can be easily accessed through various devices. This research aims to design and develop a responsive website as a centralized portal for Student Association activities and news using the Next.js framework. This study applies the Research and Development (R&D) method with the Waterfall development model, which consists of several stages, namely requirements analysis, system design, implementation, and testing to ensure that the website operates in accordance with user requirements. The system was developed using Next.js as the main framework and Tailwind CSS to support the implementation of Responsive Web Design, enabling the website to be accessed optimally on desktop, tablet, and smartphone devices. This research resulted in a system that successfully integrates news, activities, organizational profiles, and documentation into a single centralized digital platform. System testing was conducted using the Black Box Testing method by evaluating all major functions based on predetermined input and output scenarios without examining the internal structure of the program code. The test results showed that all functions operated in accordance with the specified functional requirements, achieving a 100% success rate across all testing scenarios. The developed website enables students to access centralized information on Student Association activities and news more conveniently through a wide range of devices.